Allium matinae—a new species from northwestern Iran - Friesen, Nikolai; Abbasi, Mehrdad; Murtazaliev, Ramazan; Fritsch, Reinhard M. (Phytotaxa, 2020)
Allium matinae from northwestern Iran is newly described based on morphological and molecular characters. The new species belongs to Allium sect. Daghestanica, which is distributed in three main disjunctive areas: Europe, Caucasus and China. Allium matinae shows morphological similarity with the European species of this section, despite being more related to the Caucasian species according to molecular results. The Caucasian species together with the new Iranian species show an intermediate position in A. sect. Daghestanica, which is evidenced by incongruence between nrDNA (ITS) and cpDNA trees.